Clinical and histological characterization of hair coat and glandular tissue of Chinese crested dogs. Issue 2 (18th February 2013) - Wiener, Dominique J.; Gurtner, Corinne; Panakova, Lucia; Mausberg, Theresa‐Bernadette; Müller, Eliane J.; Drögemüller, Cord; Leeb, Tosso; Welle, Monika M.
<x xml:space="preserve">Abstract</x> Background Two varieties exist in the Chinese crested dog breed, namely hairless Chinese crested dogs presenting with hypotrichosis and dentition abnormalities, and the coated powderpuffs. Hairless Chinese crested dogs are obligate heterozygotes for a FOXI3 mutation, and this phenotype is classified as a form of canine ectodermal dysplasia. Objectives We provide a detailed histological description of hair follicles and their density for the three subphenotypes (true hairless, semi‐coated and powderpuffs) of Chinese crested dogs. Apocrine and exocrine glands of the skin and other tissues were compared with findings reported from dogs with X‐linked ectodermal dysplasia. Animals Skin biopsies were collected from 22 Chinese crested dogs. Additionally, the glands of the skin and other tissues were examined from another two dogs available for postmortem examination. Methods Skin biopsies and tissues were processed, stained and evaluated in a blinded fashion. Results Hair follicular anomalies decreased with increasing number of hairs in the different phenotypes. The FOXI3 mutants had only simple primary hair follicles, whereas the nonmutant powderpuffs had compound follicles identical to other dog breeds. All Chinese crested dogs had an anagen‐dominated hair cycle. Furthermore, apocrine glands in the skin and respiratory mucous glands of the mutant Chinese crested dogs were present and normal. Conclusions and clinical importance We have identified striking histopathological differences between the three subphenotypes of Chinese crested dogs. We clearly demonstrated distinct differences between the canine ectodermal dysplasia in Chinese crested dogs and dogs with X‐linked ectodermal dysplasia.